2007
DOI: 10.1093/jnci/djk199
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Integrin α7 Mutations in Prostate Cancer, Liver Cancer, Glioblastoma Multiforme, and Leiomyosarcoma

Abstract: Integrin alpha7 appears to be a tumor suppressor that operates by suppressing tumor growth and retarding migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
87
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 23 publications
3
87
1
Order By: Relevance
“…Expression of the b 1 cytoplasmic variant, b 1C , which is downregulated in prostate cancer, completely prevents tumor growth by inhibiting IGF-IR signaling (Goel et al 2004). It has also been reported that the expression of a 7 in prostate cancer cells injected subcutaneously in SCID mice suppresses tumor growth (Ren et al 2007). This observation is relevant to the human disease as analysis of a 7 in human prostate cancer reveals that a 7 is downregulated in this type of cancer and is mutated in 57% of prostate cancers; in addition, mutations in this subunit are associated with increased cancer recurrence (Ren et al 2007).…”
Section: Tumor Growth and Metastasismentioning
confidence: 97%
See 2 more Smart Citations
“…Expression of the b 1 cytoplasmic variant, b 1C , which is downregulated in prostate cancer, completely prevents tumor growth by inhibiting IGF-IR signaling (Goel et al 2004). It has also been reported that the expression of a 7 in prostate cancer cells injected subcutaneously in SCID mice suppresses tumor growth (Ren et al 2007). This observation is relevant to the human disease as analysis of a 7 in human prostate cancer reveals that a 7 is downregulated in this type of cancer and is mutated in 57% of prostate cancers; in addition, mutations in this subunit are associated with increased cancer recurrence (Ren et al 2007).…”
Section: Tumor Growth and Metastasismentioning
confidence: 97%
“…It has also been reported that the expression of a 7 in prostate cancer cells injected subcutaneously in SCID mice suppresses tumor growth (Ren et al 2007). This observation is relevant to the human disease as analysis of a 7 in human prostate cancer reveals that a 7 is downregulated in this type of cancer and is mutated in 57% of prostate cancers; in addition, mutations in this subunit are associated with increased cancer recurrence (Ren et al 2007). Pawar et al (2007) show that growth of tumors treated with fractionated doses of irradiation (3 Gy!10 days) is inhibited in PC3 cells expressing a mutated non-cleavable form of a 6 integrin.…”
Section: Tumor Growth and Metastasismentioning
confidence: 97%
See 1 more Smart Citation
“…The expression of α6 subunit diminishes with increasing histologic grade, especially at sites of contact with the basement membrane (5). PCa demonstrates decreased positive staining for subunit α 7 , with a further decrease in metastatic disease (6). Other α subunits that have been found down-regulated include α 2 , α 4 , α 5 , and αv (2).…”
Section: Expression Of Integrins In Pca α Subunitmentioning
confidence: 99%
“…Studies have demonstrated expression of the heterodimeric complexes αvβ 3 and αvβ 6 , in PCa specimens in contrast with normal controls (10). Integrin α v β 3 has been demonstrated to increase cdc2 kinase activity and cdc2 levels in PCA (11).…”
Section: β Subunitmentioning
confidence: 99%